How much do tariffs matter? Evidence from the customs union of Belarus, Kazakhstan and Russia. Issue 2 (2nd April 2016) - Isakova, Asel; Koczan, Zsoka; Plekhanov, Alexander
Abstract : This paper provides an empirical analysis of the early impact of the formation of the customs union of Belarus, Kazakhstan and Russia, and associated changes in import schedules on the structure of imports. Relying on an original data-set of statutory tariffs we find that trade creation effects were significant only in trade between Russia and third countries, but that there was some trade destruction, with a significant negative impact on imports from China to Kazakhstan and Russia, and on imports from the EU to Belarus. However, the magnitude of this effect is relatively small, suggesting that the benefits of the new tariff policy per se are limited at best.